A Mystery of Patent Ductus Arteriosus and Serum Osmolality in Preterm Infants - Cakir, Ufuk; Tayman, Cuneyt (American Journal of Perinatology, 2019)
Objective Patent ductus arteriosus (PDA) is an important clinical problem associated with mortality and serious morbidities. It is thought that serum osmolality may affect ductal patency. We aimed to investigate the importance of serum osmolality related to ductal patency in preterm infants.Study Design Our study was conducted between January 2013 and December 2017. Premature infants with birth weight <1,500 g and gestational age <32 weeks were included in the study. Serum osmolality was compared between infants with hemodynamically significant PDA (hsPDA) and non-hsPDA.Results During the study period, 799 patients were evaluated. Mean serum osmolality levels were higher in the “hsPDA” group (297 ± 10.9 vs. 292 ± 8.3 mOsm/L) (p = 0.001). The area under the curve for osmolality was 0.582 (p = 0.0006, 95% confidence interval: 0.541–0.622) at the time of diagnosis for predicting hsPDA, with a cutoff value for osmolality of 300 mOsm/L.Conclusion Serum osmolality may be recognized as an important contributing factor for ductal patency especially among extremely preterm infants who are most likely to have hsPDA in the early days of life.
Keywords: hemodynamically significant patent ductus arteriosus; premature; serum osmolality; very low birth weight